Odnaleziony klucz - Stankowka, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
Poetycka antropologia Julii Hartwig [Julia Hartwig’s poetic anthropology] written by Marcin Terlecki is a book that fills the yawning gap in our literary understanding of the twentieth century Polish poetry and constitutes the first attempt at a comprehensive and detailed presentation of the lyrical works by J. Hartwig. The modern collection in which the work appears allow M. Terlecki to reveal the poetess’ fundamental insights dominating and underlying her world outlook and epistemological views. This, in turn, puts him in a position to give an explanation to the logic embedded in the evolution under scrutiny. M. Terlecki convincingly supports his own argument concerning J. Hartwig’s poetic reception of the world proving the thesis that its fundamentals are deeply rooted in the anthropological perspective. Terlecki differentiates the latter into three basic categories. First, there is “strangeness/alienation”, which results in the need for self-definition (determination of one’s nature and basic qualities). Then, “identity”, whose reflection turns out to be not only what is different in its external shape, but also what is different inside — within the plane of one’s own culture, biography and personality. And, finally, “empathy”, born out of questions on a feasibility of contact with what is different, alien and absent. The three categories, connected by the logic of anthropological vision, are presented as basic and fundamental for the subsequent stages in Hartwig’s poetical output. At the same time, they reveal themselves as axes of anthropological reading material provided by the author — for the discussed book is the author’s own research project on “poetic anthropology”.